Catalytic oxidative C–C bond cleavage route of levulinic acid and methyl levulinate. Issue 76 (1st August 2016) - Xia, Fei; Du, Zhongtian; Liu, Junxia; Ma, Yangyang; Xu, Jie
Abstract : The difference in the catalytic oxidative cleavage route between levulinic acid and methyl levulinate was intensively investigated. Abstract : Recently, obtaining value-added chemicals from biomass resources has attracted considerable attention. Levulinic acid is one of the most important biomass platform compounds, which could be obtained from carbohydrate biomass. In this work, levulinic acid was selectively converted into C4 product, including succinic anhydride, via catalytic oxidation with a manganese catalyst in acetic anhydride. Moreover, an unexpected product of maleic anhydride was obtained, which greatly differs from that of levulinate ester. The pathway for formation of maleic anhydride was studied by monitoring and confirming intermediates α-angelica lactone and its derivative 2-methyl-5-oxotetrahydro-2-furanyl acetate. Based on the obtained mechanistic information, the different behaviour between the oxidative cleavage of levulinic acid and levulinate ester was further discussed.